Investigating the Role of Cultural Festivals in Promoting Tourism in Developing Countries: The Case of the Ngondo Traditional Festival of Cameroon - Foncham, Elma Carmen epse Ndih Ijang (International Journal of Membrane Science and Technology, 2023)
Tourism refers to traveling for business, pleasure, or service. Cultural festivals refer to events held as a means to showcase culture and traditions. The research set out to find the role cultural festivals play in promoting tourism in developing countries, using the Ngondo Traditional Festival of Cameroon as a case study. The study is guided by a review of the literature on the role of cultural festivals in promoting tourism in developing countries, and case studies of successful cultural festivals in other developing countries. It also reviews a brief historical background, what the festival is all about, and its main aim and significance to the people of Cameroon. The research was based on casual interviews and discussions with some randomly selected tour operators, friends, colleagues, and tourists who were all part of the festival. Information was also collected from secondary sources like journals, newspapers, and from other researchers. The results of the study reveal the impact of the Ngondo festival on tourism in Cameroon, the challenges faced in promoting the festival as a tourist attraction site, and the strategies implemented to attract tourists to the festival. The study also provides recommendations that the Government and Stakeholders can use to promote the Ngondo festival. In conclusion, the festival has great potential of becoming a major source of tourism if the challenges it faces are handled properly and the necessary recommendations are implemented.